2009
DOI: 10.1038/nrg2625
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic devices for measuring gene network dynamics in single cells

Abstract: The dynamics governing gene regulation have an important role in determining the phenotype of a cell or organism. From processing extracellular signals to generating internal rhythms, gene networks are central to many time-dependent cellular processes. Recent technological advances now make it possible to track the dynamics of gene networks in single cells under various environmental conditions using microfluidic 'lab-on-a-chip' devices, and researchers are using these new techniques to analyse cellular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
215
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(215 citation statements)
references
References 128 publications
0
215
0
Order By: Relevance
“…We found that P-bodies formed rapidly in response to UV irradiation, which repeat 1 -abundance log 10 (a.u.) repeat 2 -abundance log 10 (a.u.) was in stark contrast to the delayed formation in response to MMS and HU (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…We found that P-bodies formed rapidly in response to UV irradiation, which repeat 1 -abundance log 10 (a.u.) repeat 2 -abundance log 10 (a.u.) was in stark contrast to the delayed formation in response to MMS and HU (Fig.…”
Section: Significancementioning
confidence: 99%
“…These three recent large-scale screens all relied on standard microtiter plates for imaging the yeast strains at a single time point before and after perturbation. Meanwhile, microfluidic devices emerged as powerful tools for conducting complex time-lapse experiments on small to medium scales (9,10), enabling the analysis of cellular network responses (11) and the implementation of synthetically engineered systems (12). However, it has thus far been technically impossible to interrogate thousands of continuously growing microbial strains with high spatiotemporal resolution in a single experiment.…”
mentioning
confidence: 99%
“…Given the observed IPTG and temperature dependence for wtLacI and tsLacI, we used microfluidics in conjunction with time-lapse fluorescence microscopy to examine the temporal changes in gene expression in the dual-feedback oscillator (40). The periodic induction of GFP synthesis allows monitoring the state of the oscillator circuit in individual cells.…”
Section: Single-cell Dynamics Of the Oscillator At Various Temperaturesmentioning
confidence: 99%
“…1,2 For single-cell analysis, several cell-handling methods have been developed such as microwell arrays, chemical patterning, optical tweezers, and microfluidics. [2][3][4][5] Especially, microwell arrays enable large scale arraying and high-throughput single-cell measurements of cellular responses. 6 Previous microwell array methods used gravity as a simple mechanism to trap single cells; [6][7][8][9] however, this method remains in the applications to mammalian cells for which typical volume is in the range of picoliters.…”
Section: Introductionmentioning
confidence: 99%